Multi-Faceted Role of Histone Methyltransferase Enhancer of Zeste 2 (EZH2) in Neuroinflammation and Emerging Targeting Options - Sotirios Moraitis; Christina Piperi (Biology)
Neuroinflammation, a complex nervous system response to brain injury and other pathological stimuli, exhibits a common denominator role in the pathogenesis of neurological disorders and their progression. Among several regulators of neuroinflammation, epigenetic mechanisms with particular emphasis on histone methylation have a prominent role by altering the expression of specific genes involved in the onset and progression of neuroinflammation. The Enhancer of Zeste 2 (EZH2) histone lysine methyltransferase is a multi-faceted and context-dependent regulator of immune response and neural cell function, significantly involved in the underlying mechanisms of neuroinflammation, such as inflammatory gene expression, astrocyte function, microglial activation, BBB integrity, and interactions with non-coding RNAs. Herein, we explore the intricate implication of EZH2 activity in the onset of neuroinflammation and associated pathological conditions, and discuss its potential as a therapeutic target. Currently available EZH2 inhibitors with neuroprotective effects are also addressed in an effort to reveal novel strategies for managing neuroinflammatory conditions, and potentially improving neurological health.